2019
DOI: 10.6008/cbpc2179-6858.2019.006.0024
|View full text |Cite
|
Sign up to set email alerts
|

Adubação mineral na fase produtiva da palma óleo (elaeis guineenses jacq) cultivado na região Amazônica

Abstract: A pesar da relevância socioeconomica da palma de óleo (Elaeis guineenses, Jacq) para a região norte do país, ainda são escassas as informações de adubação da cultura. O objetivo desta pesquisa foi avaliar os efeitos da adubação com nitrogênio (N), fósforo (P), potássio (K) e magnésio (Mg) na produção e estado nutricional de plantas de palma de óleo de diferentes idades. Utilizou-se o delineamento experimental em blocos ao acaso com três repetições em esquema fatorial 3 x 3 x 3 x 2, sendo três níveis de P, três… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 3 publications
10
18
0
Order By: Relevance
“…Although the levels of K fertilization showed no significant difference, B concentrations in leaves tended to decrease with an increase in K supply (Figure 2e), corroborating with the literature (Tohiruddin et al, 2010;Vié gas et al, 2019). Studies show that K fertilization decreases B absorption in oil palm plants (Rajarattnam, 1973).…”
Section: Journal Of Agricultural Studiessupporting
confidence: 88%
See 3 more Smart Citations
“…Although the levels of K fertilization showed no significant difference, B concentrations in leaves tended to decrease with an increase in K supply (Figure 2e), corroborating with the literature (Tohiruddin et al, 2010;Vié gas et al, 2019). Studies show that K fertilization decreases B absorption in oil palm plants (Rajarattnam, 1973).…”
Section: Journal Of Agricultural Studiessupporting
confidence: 88%
“…1 KCl; however, there was no difference between the fertilization levels (Figure 3e). Other studies have reported the same behavior for oil palm trees in (Dubos et al, 2011;Vié gas et al, 2019). The synergistic response of Cl to K supply is explained by the Cl content (47%) in the composition of K fertilizer.…”
Section: Journal Of Agricultural Studiessupporting
confidence: 66%
See 2 more Smart Citations
“…The use of cover crops, mainly with tropical kudzu legumes (Pueraria phaseoloides L.), is common in the cultivation of palm trees, such as coconut palm (Lins and Vié gas, 2020) and oil palm (Rodrigues et al, 2002;Vié gas et al, 2019). For the conditions of Pará , there is the recommendation of the intercropped planting of tropical kudzu and the oil palm (Vié gas and Botelho, 2007).…”
Section: Introductionmentioning
confidence: 99%